An approach to low noise amplifier optimization in Advanced Design System CAD - Galina Nikolaevna Nazarova; Vadim Vladimirovich Elesin; Denis Ivanovich Sotskov (Безопасность информационных технологий, 2016)
An approach to silicon low noise amplifier (LNA) optimization, intended for use in the CAD Advanced Design System, has been presented. The approach is based on a technique using the contour plots of LNA parameters such as operating current, transistor width, impedancematching circuit elements, minimizing the noise figure of the LNA, and providing sufficient gain and VSWR. The ability to use the models of real silicon passive and active elements, and consider the impact of the bond wires inductance is an advantage of the proposed approach. LNA optimization procedure consists of three steps. The first step is a schematic selection of the input stage LNA, specifying the operating current and providing input impedance matching. At the second step an optimization procedure with the built-in CAD optimization tools is used to calculate the contour plots of LNA parameters at one frequency point for all implementable set of values of the operating current and the input stage transistor width. Finally, optimal values of selected LNA schematic elements are defined using the calculated contour plots. The presented approach has been tested at 1,4 GHz LNA design, intended for use in a global positioning system receiver, to be implemented in a 0,35 um SOI CMOS process. The LNA provides a forward gain of 19 dB with a noise figure of only 1.6 dB, VSWR of 1,45 while drawing 60 mW from a 3,3 V supply.